Optimalisasi Tata Kelola Birokrasi Yang Efektif dan Akuntabel di Sekretariat DPRD Provinsi Jawa Barat - Annisa Syailina Hazh (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Effective and Accountable Bureaucratic Governance at the Secretariat of the Regional People's Representative Council (DPRD) of West Java Province has become the primary focus in enhancing the performance and responsiveness of local government institutions. Grounded in the principles of good governance, this improvement aims to enhance public service delivery, increase transparency, and ensure efficient resource management. This paper discusses concrete steps that can be taken, such as recording Members of the DPRD's travel reports, plenary meetings, and distributing materials for regional regulation socialization (Sosper), as well as developing effective internal oversight mechanisms. Collaboration among stakeholders is also crucial in achieving these optimization goals. It is hoped that the outcomes of this study will positively contribute to bureaucratic reform and improve governance at the local level.